SOIL ACIDITY AND SOY PHYTOMETRY (Glycine max (L.) Merrill) UNDER APPLICATION OF LIMESTONE AND AGRICULTURAL GYPSUM (Colloquium Agrariae. ISSN: 1809-8215, 2022)
The soybean is one of the main agricultural crops in Brazil, because the use of its grains is an important source of protein and vegetable oil. One of the main limiting factors for obtaining high yields in soybean in tropical soils is related to the need to correct soil acidity. The objective of the study was to evaluate the development of (Glycine max (L.) Merrill) and the variation of pH values ​​of the soil under the application of limestone and agricultural gypsum. The experimental design was completely randomized, distributed in a 4x4 factorial scheme. The treatments consisted of doses of 0, 1,5, 3,0 and 4,5 t ha-1 of only limestone, only gypsum and the combination of limestone and gypsum, repeated four times, totaling 64 experimental units. The soil pH was evaluated at 30 (pH1), 45 (pH2), 60 (pH3), 75 (pH4) days before sowing. The plant variables were: number of pods (NP), shoot green mass (SGM), shoot dry mass (SDM), root green mass (RGM), root dry mass (RDM), root length (RL) and shoot / root ratio (S/RR). The variables pH4, SGM, RL and S/RR were significantly influenced by the treatments, alone or in interaction. For pH1, pH2, pH3, NP and SDM, there were isolated effects of treatments for gypsum and limestone. At the RGM the deformation was significant for limestone and gypsum interaction with limestone. For RDM, the effect of the treatment was verified only with the use of limestone. As a conclusion, the application of limestone and gypsum reduces the soil acidity, obtaining higher pH values ​​from the doses of 3000 kg ha-1, with the combination of limestone and gypsum. The use of gypsum consortium with limestone promotes significant results in the development of soybean plants.